Control techniques for creep deformation of surrounding rock in deep underground roadways - Lijie Ge; Dong Liu; Jiaxing Tao; Zhuang Zhang; Hao Lei; Yan Zhao (PLoS ONE, 2025)
As resource extraction extends to greater depths, surrounding rock in deep underground roadways exhibits pronounced creep deformation due to the coupled effects of high in-situ stress and time-dependent behavior. Conventional support systems face significant challenges in maintaining long-term stability under such conditions. This study focuses on the pump station roadway of a mine in North China as a case study and conducts an integrated investigation involving theoretical analysis, physical modeling, and numerical simulation to develop effective creep control strategies. A theoretical framework for creep deformation control is established based on the radial stress gradient mechanism of the surrounding rock. A composite support system—comprising concrete-filled steel tube (CFST) supports, staged grouting, rock bolts, and sprayed concrete—is proposed. Using a self-developed two-dimensional physical modeling apparatus, the deformation and stress evolution of the surrounding rock are systematically compared under unsupported and composite-supported conditions, identifying key deformation zones and dominant creep patterns. Furthermore, a three-dimensional numerical model incorporating a damage-coupled creep constitutive relationship is constructed to evaluate the support system’s effectiveness in controlling roof subsidence, sidewall convergence, and plastic zone expansion. Results demonstrate that the CFST-based composite support system significantly mitigates creep-induced instability and enhances long-term roadway stability, offering theoretical and practical guidance for the design and optimization of support systems in deep soft rock roadways.